2009
DOI: 10.2139/ssrn.1564895
|View full text |Cite
|
Sign up to set email alerts
|

Choices About Competition: Differences by Gender and Hormonal Fluctuations, and the Role of Relative Performance Feedback

Abstract: Economic experiments have shown that when given the choice between piece rate and winner-take-all tournament style compensation, women are more reluctant than men to choose tournaments. These gender difference experiments have all relied on a similar framework where subjects were not informed of their relative abilities as compared to other potential competitors. I replicate these previous findings and then show that giving feedback about past relative performance moves high ability females towards more compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 38 publications
3
54
3
Order By: Relevance
“…In this literature, however, only a few tasks have been used to measure competitiveness, and these tasks can arguably be considered as more male than female. Three studies find that gender differences in competitiveness vary with the task at hand (Gneezy and Rustichini 2004b, Günther et al 2009, Grosse and Reiner 2010, whereas another study find no difference in the gender gap between a maze task and a word task (Wozniak et al 2010). Meanwhile, work in social psychology suggests that individual perceptions about relative performance, such as (over)confidence, and especially stereotypes may have important implications for actual performance (Steele 1997, Shih et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this literature, however, only a few tasks have been used to measure competitiveness, and these tasks can arguably be considered as more male than female. Three studies find that gender differences in competitiveness vary with the task at hand (Gneezy and Rustichini 2004b, Günther et al 2009, Grosse and Reiner 2010, whereas another study find no difference in the gender gap between a maze task and a word task (Wozniak et al 2010). Meanwhile, work in social psychology suggests that individual perceptions about relative performance, such as (over)confidence, and especially stereotypes may have important implications for actual performance (Steele 1997, Shih et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that culture affects important economic decisions such as labor market participation and fertility (e.g., Fernández and Fogli 2006), and the institutional setting has been found to influence competitive behavior (e.g., Balafoutas and Sutter 2010, Gneezy et al 2009, Niederle and Yestrumskas 2008, Cotton et al 2009, Niederle et al 2009, Wozniak et al 2010. For example, the gender gap in selfselection has been shown to disappear with performance feedback (Wozniak et al 2010) and the difference in performance change vanishes with repetition of the competition (Cotton et al 2009). Women have also been found to compete more than men in a matrilineal society whereas men compete more than women in a patriarchal society (Gneezy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works neutralize risk aversion by asking experiment's participants to make a choice characterized by the same risk as the tournament. In the same vein, beliefs are manipulated by changing the task performed by participants 4 (Niederle and Vesterlund, 2007;Wozniak et al, 2010) or, similarly to what we do in this paper, providing them information on their relative performance (Cason et al, 2010;Wozniak et al, 2010).…”
mentioning
confidence: 93%